2006
DOI: 10.1111/j.1365-2915.2006.00618.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of investigator disturbance in experimental forensic entomology: succession and community composition

Abstract: Carrion insect succession studies have historically used repeated sampling of single or a few carcasses to produce data, either weighing the carcasses, removing a qualitative subsample of the fauna present, or both, on every visit over the course of decomposition and succession. This study, conducted in a set of related experimental hypotheses with two trials in a single season, investigated the effect that repeated sampling has on insect succession, determined by the number of taxa collected on each visit and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 40 publications
2
20
0
Order By: Relevance
“…However, they concluded that representative insect collection from carrion does not impede the natural succession of the insects. Additionally, a subsequent study by De Jong and Hoback [18] provided further evidence that repeated sampling does not impact the qualitative assessment of the natural community of species on carrion. Thus, three pig carcasses per habitat were employed.…”
Section: Field Protocolsmentioning
confidence: 97%
“…However, they concluded that representative insect collection from carrion does not impede the natural succession of the insects. Additionally, a subsequent study by De Jong and Hoback [18] provided further evidence that repeated sampling does not impact the qualitative assessment of the natural community of species on carrion. Thus, three pig carcasses per habitat were employed.…”
Section: Field Protocolsmentioning
confidence: 97%
“…Studies on arthropods succession associated to outdoor animal remains decomposition are well documented in temperate regions (Anderson & VanLaerhoven 1996;Arnaldos et al 2001;Grassberger & Frank 2004;Tabor et al 2005;De Jong & Hoback 2006), as well as for the Neotropical region (Jirón et al 1982;Moura et al 1997;Cruz & Vasconcelos 2006;, Carvalho & Linhares 2001Iannacone 2003;Velásquez 2008;Souza et al 2008;Vasconcelos & Araujo 2012). In Colombia, studies on forensic entomology started out in 2001, and have focused mainly on patterns of decomposition in outdoor environments and aquatics conditions (Wolff et al 2001;Pérez et al 2005;Camacho 2005;Martínez et al 2007;Segura et al 2009;Grisales et al 2010;Segura et al 2011;Ramos-Pastrana & Wolff 2011;Barrios & Wolff 2011).…”
mentioning
confidence: 99%
“…The methods for weighing or qualitatively sampling the fauna were identical to those used on the destructively sampled (DS) carcasses prior to collection. “W carcasses” were only weighed on every visit, the fauna from the “P carcasses” was sampled qualitatively on every visit (10,11), and the “P&W carcasses” were weighed and qualitatively sampled on every visit. P, W, and P&W carcasses were returned to their exact position on the ground after biomass measurement or collection of insects.…”
Section: Methodsmentioning
confidence: 99%
“…Student’s t ‐tests were used to compare treatments; however, because of the numerous pairwise comparisons, the Bonferroni correction factor (α/ k , where k is the number of tests to be performed) was applied when appropriate (20,30). All raw data can be found in De Jong’s thesis (10). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation